Safety and efficacy of Panavital feed (d‐glyceric acid) for chickens for fattening. (29th April 2020) - ; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Durjava, Mojca Kos; Kouba, Maryline; López‐Alonso, Marta; Puente, Secundino López; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Panavital feed is a preparation of d ‐glyceric acid intended to be used as a zootechnical additive in chickens for fattening. The active substance (d ‐glyceric acid) of the additive ■■■■■ by fermentation with Gluconobacter frateurii . The additive is intended to be used in chickens for fattening at a concentration from ■■■■■. The FEEDAP Panel notes that the data provided for the characterisation of the active substance are incomplete and that data on the characterisation of the formulated additive are not provided. Based on the information available, the FEEDAP Panel cannot assess the qualitative and quantitative composition of Panavital feed. Due to lack of data, the safety of the production strain claimed to be used to produce the active substance cannot be evaluated. Based on the data provided by the applicant, the FEEDAP Panel cannot conclude on the safety of Panavital feed for the target species, the consumer, the user and the environment and on the efficacy of Panavital feed when used as feed additive.